Statin Effects to Reduce Hepatosteatosis as Measured by Computed Tomography in Patients With Human Immunodeficiency Virus - Lo, Janet (Open Forum Infect Dis, 2016)
Hepatosteatosis is highly prevalent among patients living with human immunodeficiency virus. In a 1-year, randomized, double-blind trial of atorvastatin or placebo, atorvastatin increased liver/spleen ratio among patients with nonalcoholic fatty liver disease, indicating a reduction in hepatosteatosis. This reduction in hepatosteatosis is associated with reduction in low-density lipoprotein cholesterol with statin therapy.